Exploration of Plants Utilization for Traditional Medicine by the Dayak Laya Sub-tribe in Petuo Hamlet, West Kalimantan, Indonesia - Putri Putri; Syamswisna Syamswisna; Hayatul Fajri (Jurnal Ilmu Kehutanan, 2026)
The Dayak Laya sub-tribe in Petuo Hamlet maintains traditional knowledge of medicinal plants for healthcare. This research aimed to explore the medicinal plants traditionally used by them. A qualitative approach was adopted in this research. Primary data were collected through semi-structured interviews, field observations, and documentation. Informants were selected using a snowball sampling. Secondary data was collected through literature reviews to enrich the primary data. Meanwhile, plant specimens were collected and identified using standard taxonomic references. The results showed that 32 medicinal plant species from 21 families were used by the Dayak Laya sub-tribe, with Zingiberaceae as the most dominant family. Leaves were the most frequently used for medicine, while boiling was the predominant method of preparation. Medicinal plants were primarily administered orally, but topical applications were also observed. The selection and use of plant species were influenced by factors such as availability, cultural practices, and perceived efficacy. The Dayak Laya sub-tribe possesses diverse ethnobotanical knowledge that remains actively practiced. This research reports the importance of documenting and analyzing traditional medicinal knowledge as a basis for preservation and as a potential resource for future pharmacological development.